The Bloomsbury handbook of the Spanish Civil War - Cazorla Sánchez, Antonio 1963- Herausgeber; Ribeiro de Menezes, Alison, 1969- 1969- Herausgeber; Shubert, Adrian, 1953- 1953- Herausgeber (Bloomsbury Handbooks, 2023)
In 25 innovative thematic essays, The Bloomsbury Handbook of the Spanish Civil War sees an interdisciplinary team of scholars examine a conflict that, more than 80 years after its conclusion, continues to generate both scholarly and public controversy. Split into four main sections covering Military and Diplomatic Issues, Society and Culture, Politics, and Debates, the volume offers a number of unique features. It is unprecedented in its comprehensiveness and includes chapters on topics that are rarely, if ever, explored in the literature of the field: humanitarianism, children and families, material conditions, the decimation of elites, archives and sources, archaeological approaches, digital approaches, public history, and cultural studies approaches. Instead of discussing each of the two warring sides, Republicans and Francoists, separately, as is so often the case, the book's thematic structure means that these opposing forces are examined together, facilitating comparison and fresh understanding in numerous areas of study. Contributors from the UK, the USA, Canada, Spain and Denmark also analyse the major controversies and disputes surrounding each topic as part of a detailed exploration of one of the seminal events of the 20th century